SITOSTEROLEMIA – RARE CAUSE OF HYPERCHOLESTEROLEMIA IN CHILD - Antoneta Dacia Petroaie (Journal of Experimental and Molecular Biology, 2019)
Sitosterolemia is a rare autosomal recessive disorder caused by mutations in ABCG5 or ABCG8, leading to increased intestinal absorption and to a diminution of the biliary excretion of plant sterols (sitosterol, campesterol, stigmasterol) and cholesterol. We report a sitosterolemia case of a little girl with severe hypercholesterolemia at the age of 11 months. The occurence of the some linear xanthoms at the level of the Achilles tendon, bilaterally and the extremely high cholesterol (total cholesterol: 949.6 mg%, LDL-cholesterol: 837 mg%) have constituted the starting point for subsequent investigations. Cardiac and abdominal ultrasound does not have pointed out the changes. No family history of hypercholesterolemia has been reported. Completing genetic tests confirmed the diagnosis of sitosterolemia. By sequencing the entire genome two mutations were detected in the ABCG5 gene (Q16X and R446X). We present this clinical case due to the rarity and particularity of the disease. Genetic tests play the most important role in diagnosing the disease and in an appropriate therapeutic approach for the child patient. Proper diet and family responsibility is the key to dispensing the case and to avoiding complications.